Efforts To Improve Student Activities and Results Using The Guided Inquiry Learning Model In Class IX Students of SMP Negeri 9 Kendari - Fridawati Ramli (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2023)
This study aims to increase student learning activities and outcomes in social studies subjects by applying the guided inquiry learning model. This research was conducted in class IX at SMP Negeri 9 Kendari in the 2019/2020 academic year's odd semester. The subjects studied were students of class IX-10, totalling 35 students, with details of 23 male students and 12 female students. This research was carried out in 2 (two) cycles: (a) planning; (b) implementation of actions; (c) observation; and (d) reflection. The data obtained were analyzed using descriptive statistics. The results showed: (1) the value of student activity with the application of the guided inquiry learning model: in cycle I, there were 7 (20%) students out of 35 getting grades in the outstanding category, increasing in cycle II to 24 (68.57) students in the "outstanding" category. Students who scored in the excellent category in the first cycle were 12 (34.29%), but that number decreased in the second cycle; there were only 7 (20%) students in the excellent category. Students who scored in the less category in cycle I, namely 16 (45.71%) students out of 35 students, decreased in cycle II, there were only 4 (11.43%) students, and in cycle, I and cycle II, no students scored in the less category; and (2) student learning outcomes increased from the pre-action results, namely, out of 35 students, only nine (25.71%) students had achieved the KKM. Increased the cycle, I test results showed 22 students (62.86%) who had completed KKM and increased again in cycle II to show 31 students (88.57%) who had achieved KKM.